Texture technique to simultaneously achieve large electric field induced strain response and ultralow hysteresis in BMT-PMN-PT relaxor ferroelectric ceramics. (1st March 2022) - Jia, Hongrui; Liang, Zhigang; Li, Zhen; Li, Fei; Wang, Linghang
Abstract: Piezoelectric ceramics with large strain response and low hysteresis are highly desired for high precision displacement actuator applications. In this work, we report the simultaneous achievements of large strain response and ultralow hysteresis in [001]c oriented Bi(Mg1/2 Ti1/2 )O3 -Pb(Mg1/3 Nb2/3 )O3 -PbTiO3 textured ferroelectric ceramics. X-ray diffraction and field-emission scanning electron microscopy were used to reveal the microstructure evolution process of textured ceramics during texture development. A large electric-field induced strain of 0.39% at 7 kV/mm and a ultralow hysteresis of 1.94% were achieved in textured ceramics with texture degree 90%. The as-prepared textured ceramics have a relatively good temperature stability, and the strain value varies from 0.36% to 0.29% at 6 kV/mm in the temperature range of 20-100 °C. This novel textured ceramics with a large strain and ultralow hysteresis will further provide a promising candidate for the application of large-displacement piezoelectric actuator with high precision displacement. Graphical Abstract: Image, graphical abstract